2017
DOI: 10.1038/s41467-017-01444-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal hyperactivity due to loss of inhibitory tone in APOE4 mice lacking Alzheimer’s disease-like pathology

Abstract: The ε4 allele of apolipoprotein E (APOE) is the dominant genetic risk factor for late-onset Alzheimer’s disease (AD). However, the reason APOE4 is associated with increased AD risk remains a source of debate. Neuronal hyperactivity is an early phenotype in both AD mouse models and in human AD, which may play a direct role in the pathogenesis of the disease. Here, we have identified an APOE4-associated hyperactivity phenotype in the brains of aged APOE mice using four complimentary techniques—fMRI, in vitro ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 84 publications
6
141
1
Order By: Relevance
“…As the endosomal-lysosomal dysregulation that we observed in the brains of aged APOE4 mice was not restricted to the EC 30 , this may play a role in the APOE4-associated bioenergetic deficits that we observed in the Hip and Ctx of these mice. On the other hand, the neuronal hyperactivity that we observed appears to be primarily localized to the EC within the hippocampal formation 33 . Intriguingly, neuronal activity and glucose utilization have previously been shown to exist in a near 1:1 stoichiometric relationship 72 , suggesting that the bioenergetic counterbalancing that we observe in the EC of aged APOE4 mice may be directly correlated to the observed neuronal hyperactivity in these mice 33 .…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…As the endosomal-lysosomal dysregulation that we observed in the brains of aged APOE4 mice was not restricted to the EC 30 , this may play a role in the APOE4-associated bioenergetic deficits that we observed in the Hip and Ctx of these mice. On the other hand, the neuronal hyperactivity that we observed appears to be primarily localized to the EC within the hippocampal formation 33 . Intriguingly, neuronal activity and glucose utilization have previously been shown to exist in a near 1:1 stoichiometric relationship 72 , suggesting that the bioenergetic counterbalancing that we observe in the EC of aged APOE4 mice may be directly correlated to the observed neuronal hyperactivity in these mice 33 .…”
Section: Discussionmentioning
confidence: 51%
“…Taken together, our data suggest that, in contrast to other brain region such as the hippocampus and cortex, the EC of aged APOE4 mice exhibits an increased rate of oxidative metabolism and ATP turnover, as compared to aged APOE3 mice. We hypothesize that this differential regional mitochondrial respiration that we observe here is downstream of the decreased glucose utilization observed in APOE4 carriers [16][17][18] and may be related to the neuronal hyperactivity that we observed in the EC of aged APOE4 mice 33 . In addition, we hypothesize that the unique bioenergetic compensatory mechanisms that we observe in the EC may lead to an increased rate of Table 3.…”
Section: Metabolitementioning
confidence: 55%
See 1 more Smart Citation
“…These results demonstrated that blocking neuron surface glycans with AAL and WGA induced the hyperexcitability of hippocampal neurons. It has been reported that neuronal hyperactivity is an early phenotype in Alzheimer’s disease and could trigger apoptosis of neurons(Abiega et al , 2016; Nuriel et al , 2017). Our results demonstrated that declined glycosylation on the cell surface of hippocampal neurons can induce hyperexcitability and further apoptosis, which implied the important role of glycosylation in the pathogenesis of the Alzheimer’s disease.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ApoE4 is a specific and severe NMDA receptor functional suppressor at the postsynaptic membrane. Accordingly, undue amplification of weak excitatory signals has been reported for ApoE4 knock-in mice (Nuriel et al, 2017). This compensatory phenotype is likely related to the substantially elevated Aβ levels shared by ApoE4 knock-in mice (Liraz et al, 2013), ApoE4/APPind mice (Bales et al, 2009) and human ApoE4 carriers (Monsell et al, 2015).…”
Section: Apoe Polymorphisms Are Predominant Risk Factors For Spomentioning
confidence: 98%